2022
DOI: 10.3390/medicina58060834
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Laparoscopic Gastrectomy for Gastric Cancer: An Updated Systematic Review

Abstract: Background and Objectives: Gastrectomy with D2 lymphadenectomy is the standard surgical treatment with curative intent for patients with gastric cancer (GC). Over the last three decades, surgeons have been increasingly adopting laparoscopic surgery for GC, due to its better short-term outcomes. In particular, laparoscopic gastrectomy (LG) has been routinely used for early gastric cancer (EGC) treatment. However, LG suffers from technical limitations and drawbacks, such as a two-dimensional surgical field of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Robotic surgery has gained popularity and significance in MIS over the last few years and clinicians hope to further expand on the recognized advantages of the laparoscopic surgical technique for patients [ 7 ]. In this context, many scientific papers have reported on patient outcomes and surgical data when applying robotic surgery which has been summarized in recent systematic reviews [ 8 , 9 ]. In addition, it is presumed that robotic surgery provides ergonomic benefits for surgeons by reducing physical demands [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery has gained popularity and significance in MIS over the last few years and clinicians hope to further expand on the recognized advantages of the laparoscopic surgical technique for patients [ 7 ]. In this context, many scientific papers have reported on patient outcomes and surgical data when applying robotic surgery which has been summarized in recent systematic reviews [ 8 , 9 ]. In addition, it is presumed that robotic surgery provides ergonomic benefits for surgeons by reducing physical demands [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For early GC, surgical treatment is mainly performed in clinical practice[ 12 ]. Open surgery can directly remove the focus lesion; however, it results in higher incidence of complications owing to large trauma, more intraoperative bleeding, long recovery time, poor prognosis, complex tissue structure around the stomach, difficult operation procedure, and long exposure time of the organs[ 13 , 14 ]. Therefore, developing a surgical method with less trauma, quick recovery, and minimal impact on immunity is of great practical importance.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of time to first flatus in robotic gastrectomy versus laparoscopic gastrectomy revealed a range of findings among the 15 studies that examined it. Overall, nine out of the 15 studies reported a statistically significant decrease in time to the first flatus, in favor of the robotic approach [ 5 , 7 , 8 , 23 , 15 , 26 , 29 , 30 , 34 ]. Notably, Bobo et al [ 7 ] concluded that the time to first postoperative flatus was 0.14 days shorter for the robotic group, with Jin et al [ 29 ] and Yu et al [ 8 ] further backing up this claim (-0,105 and -0.16 days, respectively).…”
Section: Reviewmentioning
confidence: 99%
“…Regarding the time required to initiate oral intake, a clear trend across the eleven studies is evident. Ten studies [ 5 , 8 , 10 , 17 , 24 , 26 , 27 , 30 , 32 , 34 ] concluded that the patients who underwent robotic gastrectomy initiated oral intake earlier than those in the laparoscopic cohorts. Particularly, Guerrini et al reported that the robotic group required 4.25 days to initiate oral intake, while the laparoscopic required 4.45 days [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation